DEVELOPMENT OF COGNITIVE ACTIVITY OF PUPILS OF BASIC SCHOOLS IN THE TEACHING OF PHYSICAL EDUCATION - Natalia Mukhanova (Вестник Северо-Кавказского федерального университета)
In pedagogy knowledge is the primary means of developing cognitive activity of students, and in the process of physical education is traditionally considered to be a panacea for solving all problems of physical training at school, including the development of cognitive activity ofstudents is a specially selected means based on the students ' execution of motor activity. The authors present their vision of formation of cognitive activity on the basis of wide use of educational potential of academic subject «Physical education».